In situ growth of [hk1]-oriented Sb2S3 for solution-processed planar heterojunction solar cell with 6.4% efficiency - Jin, Xin (2021)
Binary compound antimony sulfide (Sb2S3) with its nontoxic and earth-abundant constituents, is a promising light-harvesting material for stable and high efficiency thin film photovoltaics. The intrinsic quasi-1D (Q1D) crystal structure of Sb2S3 is known to transfer photogenerated carriers rapidly along the [hk1] orientation. However, producing Sb2S3 devices with precise control of [hk1] orientation is challenging and unfavorable crystal orientations of Sb2S3 result in severe interface and bulk recombination losses. Herein, in situ vertical growth of Sb2S3 on top of ultrathin TiO2/CdS as the electron transport layer (ETL) by a solution method is demonstrated. The planar heterojunction solar cell using [hk1]-oriented Sb2S3 achieves a power conversion efficiency of 6.4%, performing at almost 20% higher than devices based on a [hk0]-oriented absorber. This work opens up new prospects for pursuing high-performance Sb2S3 thin film solar cells by tailoring the crystal orientation.